2019
DOI: 10.12669/pjms.35.4.1003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ferritin levels and inflammatory markers on HbA1c in the Type 2 Diabetes mellitus patients

Abstract: Objective: Diabetes Mellitus (DM) is a significant public health issue worldwide due to the associated comorbidities. Recent studies have demonstrated a strong relationship between blood glucose levels and serum ferritin levels in patients with type 2 DM. The aim of the study was to investigate the association between Ferritin Levels and Inflammatory Markers on HbA1c in the Type 2 Diabetes Mellitus Patients. Methods: This single-center, cross-sectional, controlled study included patients who were admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Our results support previous studies that suggested the association of CRP with an increased risk of diabetes and metabolic syndrome. 14 Sex, HDL-cholesterol level, income, and smoking status were not significant. The explanatory power increased with additional adjustments from Model 1 (R 2 =0.0364) to Model 2 (R 2 =0.0638) and Model 3 (R 2 =0.0717).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our results support previous studies that suggested the association of CRP with an increased risk of diabetes and metabolic syndrome. 14 Sex, HDL-cholesterol level, income, and smoking status were not significant. The explanatory power increased with additional adjustments from Model 1 (R 2 =0.0364) to Model 2 (R 2 =0.0638) and Model 3 (R 2 =0.0717).…”
Section: Discussionmentioning
confidence: 82%
“…These results suggest an association between blood sugar levels and inflammation in diabetic patients, similar to previous studies. 14 In a study on the relationship between hs-CRP and insulin resistance in type 2 diabetic patients, it was reported that relatively increased hs-CRP in type 2 diabetic patients was associated with increased insulin resistance, even in the normal range. 15 Currently, the hypothesis explaining the relationship between markers of inflammatory response and insulin resistance is that chronic inflammation can act as an inducer of insulin resistance or stimulate hs-CRP synthesis by an underlying disease, eventually leading to type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fatal outcomes by COVID-19 are accompanied by cytokine storm syndrome, thereby it has been suggested that disease severity is dependent of the cytokine storm syndrome 2 . Many individuals with diabetes exhibit elevated serum ferritin levels [3][4][5] , and it is known that they face a higher probability to experience serious complications from COVID-19 6 . On this basis, we briefly review evidence supporting the hypothesis that ferritin levels might be a crucial factor influencing the severity of COVID-19.…”
Section: To the Editormentioning
confidence: 99%
“…Manipulations decreasing dietary iron should be also considered as they have been shown to modify serum ferritin levels 14,15 . Thus we hypothesized that this might reduce the exacerbation of COVID-19, specially in individuals with morbidities cursing with elevated ferritin levels such as diabetes [3][4][5] .…”
Section: To the Editormentioning
confidence: 99%
“…Ideally, serum ferritin levels might be a crucial factor influencing the severity of COVID-19. Many individuals with diabetes exhibit elevated serum ferritin levels, facing a higher probability of experiencing severe complications from COVID-19 [6]. The median values of serum ferritin levels from a few recent studies exceeded the upper limit of detection in the COVID-19 patients during all the days of hospitalization, suggesting that ferritin levels increased incessantly throughout the hospital stay [7].…”
Section: Introductionmentioning
confidence: 99%